PRODUCTIVE AND ECONOMICAL VARIETIES OF ORDINARY RASPBERRIES (RUBUS IDAEUS L.) IN THE CONDITIONS OF THE CHUI VALLEY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article contains the results of research of productive and economical varietiesof ordinary raspberries (Rubus Idaeus L.) cultivated in the conditions of the Chui Valley. The subject of the study was four varieties of an ordinary raspberry - suburban, Babier Summer, Barnauland Kuzmin's news. The main goal of scientific research is to determine the highly productivevarieties of raspberries in the conditions of the Chui Valley and to distinguish promising varietiesfor implementation in production, which are characterized by good economic efficiency. Here,the costs of planting material, fertilizers, plant protection products, fuel and lubricants, harvestingand other work related to caring for plants were taken into account, and calculations with pricesof 2014-2016 were carried out. According to the complex of signs, two promising varieties can bedistinguished the best for cultivation in industrial conditions in the Chui Valley of the Republic.
Keywords: productivity, common raspberry, berry size, fruit twigs, profitability.